WIRAUSAHAWAN MAHASISWA DI PROVINSI ACEH: KENDALA DAN FAKTOR PENENTU KESUKSESAN - Jullimursyida Jullimursyida (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2019)
The purpose of this study was to identify factors that contribute to the success of student entrepreneurs in Aceh from the aspect of the desire for achievement, locus of control, self-efficacy, instrumental readiness and subjectives norm. This research is quantitative research which applied the survey approach to be able to determine the factors that influence the success of entrepreneurs among students. The results indicates that the need for achievement, locus of control, self efficacy, instrumental readiness and subjectives norm can explain the interest of students to become entrepreneurs in Aceh . The results of this study will hopefully help to clarify aspects of the development of entrepreneurship among the students that will enrich their knowledge of entrepreneurship especially among the students in Indonesian. The result of this study believed that by getting the answers to these questions, it will be able to take a step closer to finding ways to increase the number of students to become entrepreneurs.